Cultural incorporation of the Kirby-Bauer method in introductory microbiology lab - Ashley McCarley; Caryl Ann Becerra (Journal of Microbiology & Biology Education)
ABSTRACT With rising antibiotic resistance, researchers are exploring sourced pharmaceuticals from local plant materials. One avenue is medicinal plants used in Indigenous communities. California State University, Channel Islands (CSUCI), is built on unceded Chumash land, affording collaboration with local Chumash communities to steward the land’s natural and cultural ancestry. Utilizing plant extracts derived from California plant species, we developed an exercise incorporating the local cultural heritage and Kirby-Bauer disk diffusion assay (KB assay). In this exercise, students discuss impacting antibiotic resistance and the role of holistic discovery in creating new pharmaceuticals, examining cultural and familial teachings as a source of scientific/academic inquiry. Students then perform KB assays using plant extracts alongside antibiotics, interpret zones of inhibition for each disk, and compare them to susceptibility cutoffs provided by their lab manual and Clinical and Laboratory Standards Institute (CLSI). While most plant extracts proved ineffective against bacterial strains, students engaged in a novel method for a standardized microbiology technique. Using plants accessed from local environments expands the exercise to various regions, utilizing local flora or ingredients in their classrooms.